2020
DOI: 10.1070/qel17205
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hydrothermal synthesis conditions on up-conversion luminescence intensity of β-NaYF4 : Er3+, Yb3+ submicron particles

Abstract: The differences in the luminescence intensities of up-conversion β-NaYF4 : Er3+, Yb3+ particles synthesised by the hydrothermal method under various synthesis conditions are studied. The results of the study lead to the conclusion that in order to achieve the maximum luminescence intensity in such particles, it is necessary to use ammonium fluoride and a medium with pH = 3. In this case, the length of the particles increases, up to the formation of rod-shaped particles. Based on the data on the size of the coh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The UCNPs were synthesized by our variant of the hydrothermal method [24] according to the technology developed by us (Supplementary File S1). In this case, an increased concentration of citric acid was used, but the amount of sodium in the citrate composition was stoichiometric.…”
Section: Synthesis and Size Characterisation Of Ucnpsmentioning
confidence: 99%
See 2 more Smart Citations
“…The UCNPs were synthesized by our variant of the hydrothermal method [24] according to the technology developed by us (Supplementary File S1). In this case, an increased concentration of citric acid was used, but the amount of sodium in the citrate composition was stoichiometric.…”
Section: Synthesis and Size Characterisation Of Ucnpsmentioning
confidence: 99%
“…To obtain an in vitro mixed suspension with a given concentration of cells and NPs, we used a suspension in a physiological solution of synthesized NaYF4:Yb,Er NPs with an average size of 80 nm (Figure 1). Four types of NPs were used: Type 1.-Synthesized NaYF4 particles "as is", coated with citrate anions as the synthesis was performed out using sodium citrate; Type 2.-NaYF4 particles annealed at a temperature of 500°С to remove citrate anions from the surface [24]; Type Type 1.-Synthesized NaYF 4 particles "as is", coated with citrate anions as the synthesis was performed out using sodium citrate; Type 2.-NaYF 4 particles annealed at a temperature of 500 • C to remove citrate anions from the surface [24]; Type 3.-NaYF 4 particles coated with SiO 2 [34]; Type 4.-NaYF 4 particles coated with HSA molecules and Methylene Blue.…”
Section: Rbc Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the majority of these techniques require a high reaction temperature, reduced atmosphere, complex operation process, and longer duration and may lead to the aggregation of the nanoparticles. Moreover, the synthesis conditions including solvent, temperature, reaction time, and concentration play an important role in determining the phase and size of the prepared particles [30][31][32]. Based on the reported studies hitherto, the phase and size of the upconversion particle were found to play an important role in determining the emission properties of the prepared particles [33][34][35].…”
Section: Introductionmentioning
confidence: 99%